Challenges for Central Banking : Perspectives from Latin America - Jacome H., Luis I.; Carriere-Swallow, Yan.; Faruqee, Hamid; Srinivasan, Krishna (Washington, D.C. : International Monetary Fund, 2016)
In the wake of the 2008-09 global financial crisis, central banking and monetary policy in many corners of the world came under intense pressure and entered unchartered waters. The breadth and scale of central bank operations have been modified or expanded in unprecedented and even unimaginable ways given the circumstances. Additionally, a fundamental rethinking of central banking and its policy frameworks has been taking place. This volume reflects a multilateral effort to help close the gap in our knowledge in meeting the critical challenges presented by these significant changes, in particular, those confronting central banks in Latin America. The volume's first section provides a panoramic overview of the policy progress made to date and the challenges that lie ahead. The related issue of spillovers and monetary independence is taken up more fully in the next section. The final section presents chapters that reexamine macroprudential and monetary policies and policy frameworks from the perspective of central bank staff members from the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet